(untitled) - DeSpelder, Lynne Ann (New York, 2011)
The Last Dance offers an interdisciplinary approach to the study of death and dying. Integrating the experiential, scholarly, social, individual, emotional, and intellectual dimensions of death and dying, this acclaimed text provides solid grounding in theory and research, as well as practical application to students' lives. The ninth edition has been updated to offer cutting-edge and comprehensive coverage of death studies.
Keywords: Tử vong,Death; Khía cạnh tâm lý,Psychological aspects